Vestiges of war the Philippine-American War and the aftermath of an imperial dream, 1899-1999 - Shaw, Angel Velasco; Francia, Luis 1945- (New York University Press, 2002)
U.S. intervention in the Philippines began with the little-known 1899 Philippine-American War. Using the war as its departure point in analyzing U.S.—Philippine relations, Vestiges of War retrieves this willfully forgotten event and places it where it properly belongs—as the catalyst that led to increasing U.S. interventionism and expansionism in the Asia Pacific region. This seminal, multidisciplinary anthology examines the official American nationalist story of "benevolent assimilation" and fraternal tutelage in its half-century of colonial occupation of the Philippines. Integrating critical and visual art essays, archival and contemporary photographs, dramatic plays, and poetry to address the complex Philippine and U.S. perspectives and experiences, the essayists compellingly recount the consequences of American colonialism in the Philippines. Vestiges of War will force readers to reshape their views on what has been a deliberately obscure but significant phase in the histories of both countries, one which continues to haunt the present.